Circulating Serum Cystatin C as an Independent Risk Biomarker for Vascular Endothelial Dysfunction in Patients with COVID-19-Associated Multisystem Inflammatory Syndrome in Children (MIS-C): A Prospective Observational Study - Kreslová, Marcela; Jehlička, Petr; Sýkorová, Aneta; Rajdl, Daniel; Klásková, Eva; Prokop, Pavel; Kaprálová, Sabina; Pavlíček, Jan; Kaslová, Romana; Palátová, Alžběta; Mohylová, Veronika; Sýkora, Josef (Biomedicines, 2022)
INTRODUCTION: Multisystem inflammatory syndrome in children (MIS-C) is a new clinical entity that has emerged in the context of the COVID-19 pandemic. Despite the less severe course of the disease, varying degrees of cardiovascular events may occur in MIS-C; however, data on vascular changes occurring in MIS-C are still lacking. Endothelial dysfunction (ED) is thought to be one of the key risk factors contributing to MIS-C. BACKGROUND: We conducted a prospective observational study. We investigated possible manifestations of cardiac and endothelial involvement in MIS-C after the treatment of the acute stage and potential predictive biomarkers in patients with MIS-C. METHODS: Twenty-seven consecutive pediatric subjects (≥9 years), at least three months post-treated MIS-C of varying severity, in a stable condition, and twenty-three age- and sex-matched healthy individuals (HI), were enrolled. A combined non-invasive diagnostic approach was used to assess endothelial function as well as markers of organ damage using cardiac examination and measurement of the reactive hyperemia index (RHI), by recording the post- to pre-occlusion pulsatile volume changes and biomarkers related to ED and cardiac disease. RESULTS: MIS-C patients exhibited a significantly lower RHI (indicative of more severe ED) than those in HI (1.32 vs. 1.80; p = 0.001). The cutoff of RHI ≤ 1.4 was independently associated with a higher cardiovascular risk. Age and biomarkers significantly correlated with RHI, while serum cystatin C (Cys C) levels were independently associated with a diminished RHI, suggesting Cys C as a surrogate marker of ED in MIS-C. CONCLUSIONS: Patients after MIS-C display evidence of ED, as shown by a diminished RHI and altered endothelial biomarkers. Cys C was identified as an independent indicator for the development of cardiovascular disease. The combination of these factors has the potential to better predict the cardiovascular consequences of MIS-C. Our study suggests that ED may be implicated in the pathophysiology of this disease.
Keywords: cystatin C; reactive hyperemia index; coronavirus disease 2019; severe acute respiratory syndrome coronavirus 2; multisystem inflammatory syndrome; asymmetric dimethylarginine; endothelial dysfunction; atherosclerosis; biomarkers